Exploring the Link between Moral Reasoning and Behavioral Action among Young Children in Zimbabwean - Mbokochena, Edmore; Mudzengerere, Fungai Hamilton; Chikwiri, Elizabeth (EDUCARE, 2014)
ABSTRACT: This study explored the link between moral reasoning and behavioral action among young Zimbabwean children aged between 9 and 13 years (grade 3 â grade 7). The ultimate aim of the study was to see if sound moral reasoning leads to sound behavioral action. Such a study takes lofty significance given moral ills, such as child sexual abuse currently pervading and disintegrating the Zimbabwean society. The survey research design was used. Participants, who completed a questionnaire on moral reasoning and behavioral action, were 120 at grade 3 â grade 7 pupils randomly selected from one school in one of Harareâs high density suburbs. The results of this study showed that for the majority of the pupils (83.3%), moral reasoning was not linked to behavioral action. While the majority (90%) reported that it was strong to talk during the teacherâs absence, most of the pupils (83.3%) said that they would not tell the teacher the truth, arguing that it was wrong to betray fellow pupils. More 12-13 years old (20.8%) than 9-11 years old (9.7%) felt it is necessary to tell the teacher the truth. The study helps those individuals and institutions dealing with children to be cautious about childrenâs testimonies since some of them lie. Furthermore, the results of this study task the society with the responsibility of ensuring that high moral values such as justice, fairness, truthfulness, trustworthiness, and so on are not only understood by children, but are also practiced by children if society is to remain habitable.KEY WORDS: Moral, children, teacher, behavioral, reasoning, justice, fairness, truthfulness, trustworthiness, action, and Zimbabwean society.Â Â Â Â About the Authors: Edmore Mbokochena is a Lecturer at the Department of Psychology, Womenâs University in Africa, Harare, Zimbabwe; Fungai Hamilton Mudzengerere is a Research Fellow at the National University of Science and Technology, Bulawayo, Zimbabwe; and Elizabeth Chikwiri is a Dean of Studies at the Womenâs University in Africa, Harare, Zimbabwe. Corresponding e-mail: eddiembok@gmail.comHow to cite this article? Mbokochena, Edmore, Fungai Hamilton Mudzengerere & Elizabeth Chikwiri. (2014). âExploring the Link between Moral Reasoning and Behavioral Action among Young Children in Zimbabweanâ in EDUCARE: International Journal for Educational Studies, Vol.7(1) August, pp.1-6. Bandung, Indonesia: Minda Masagi Press and UMP Purwokerto, ISSN 1979-7877.Chronicle of the article: Accepted (June 27, 2014); Revised (July 14, 2014); and Published (August 17, 2014).